Regional integration in Latin America: historical developments, current challenges, especially in Mercosur - Almeida, Paulo Roberto de (2018)
Historical essay dealing with the regional processes of economic integration in Latin America, following the main phases of attraction and repulsion in those experiments; main challenges for the accomplishments of that integration have been industrialization efforts by countries, characterized by protectionist trade and industrial policies, defense of national sovereignty, and also rules presiding the multilateral trade system during the initial phase of Gatt; reforms in that system, allowing for some flexibility in the reciprocity clauses, started a new phase in that process, opening the way for a sub-regional approach in the integration agreements; Brazil and Argentina decided to create Mercosur, with a customs union framework to arrive at a common market objective; despite some progresses, the project is still unfinished.